From Doctrinal Legitimacy to Child Protection: Mapping and Reconstructing Child Marriage Fiqh Studies in Indonesia - Sriharini; Ahmad Izudin; Agus Suprianto; Abrori; Mohammad Ridwan (Journal of Islamic Law, 2026)
This article examines the evolution of child marriage fiqh (Islamic jurisprudence) scholarship in Indonesia and argues for a paradigmatic shift from doctrinal legitimacy toward substantive child protection. Although academic discussions on child marriage have expanded significantly over the past decade, much of the scholarship remains anchored in doctrinal–juridical frameworks that prioritize formal permissibility and legal validity over children’s welfare. This study aims to map the epistemological trajectory of child marriage fiqh critically and to reconstruct its normative orientation toward a preventive and child-centered paradigm. Employing a qualitative systematic desk review, the research analyzes 68 peer-reviewed articles published in 22 Scopus-indexed Islamic law journals between 2017 and 2026. The findings reveal methodological disparities, thematic fragmentation, and geographic concentration, alongside recurring critiques of classical fiqh doctrines that continue to legitimize marriage dispensation practices. Despite increasing references to the objectives of Islamic law (maqāṣid al-sharīʿah) and child protection principles, most studies remain confined to descriptive and doctrinal approaches, with limited socio-legal and interdisciplinary integration. Consequently, contemporary fiqh discourse reproduces a legality-centered approach rather than developing a preventive jurisprudence grounded in the best interests of the child. By providing the first systematic intellectual mapping of this field, the article advances a critical-progressive framework that integrates maqāṣid reasoning, socio-legal analysis, and judicial practice to strengthen child protection within Indonesia’s plural Islamic legal order. [Artikel ini mengkaji evolusi studi fikih perkawinan anak di Indonesia dan berargumen perlunya pergeseran paradigmatis dari legitimasi doktrinal menuju perlindungan anak secara substantif. Meskipun diskursus akademik mengenai perkawinan anak meningkat secara signifikan dalam satu dekade terakhir, sebagian besar kajian masih bertumpu pada kerangka doktrinal-yuridis yang memprioritaskan kebolehan formal dan keabsahan hukum dibandingkan kesejahteraan anak. Penelitian ini bertujuan untuk memetakan secara kritis trajektori epistemologis kajian fikih perkawinan anak serta merekonstruksi orientasi normatifnya menuju paradigma preventif yang berpusat pada anak. Dengan menggunakan pendekatan desk review sistematis kualitatif, penelitian ini menganalisis 68 artikel terindeks Scopus yang diterbitkan dalam 22 jurnal hukum Islam pada periode 2017–2026. Temuan penelitian menunjukkan adanya disparitas metodologis, fragmentasi tematik, dan konsentrasi geografis, disertai kritik berulang terhadap doktrin fikih klasik yang masih melegitimasi praktik dispensasi perkawinan. Meskipun wacana maqāṣid al-sharīʿah dan perlindungan anak semakin menguat, mayoritas studi tetap berada dalam pendekatan deskriptif dan doktrinal, dengan integrasi sosio-legal dan interdisipliner yang terbatas. Akibatnya, diskursus fikih kontemporer cenderung mereproduksi legalitas normatif daripada mengembangkan yurisprudensi preventif berbasis kepentingan terbaik anak. Melalui pemetaan intelektual sistematis, artikel ini menawarkan kerangka kritis-progresif yang mengintegrasikan maqāṣid, analisis sosio-legal, dan praktik peradilan guna memperkuat perlindungan anak dalam tata hukum Islam Indonesia.]